INSURANCE SERVICE PURCHASE DECISION-MAKING RATIONALE: EXPERT-BASED EVIDENCE FROM LITHUANIA - Ulbinaitė, Aurelija; Kučinskienė, Marija (Ekonomika, 2013)
Abstract. This paper deals with the examination of the rationale for insurance service purchase decision making with a focus on Lithuania and its possible implications for both Lithuania and other developing insurance markets. This work proposes a model that reflects the several stages of the insurance service purchase decision making process, including the time dimension. This model is constructed on the basis of three hypotheses; these hypotheses are tested based on data collected by means of an insurance expert survey. The results confirm the existence of two stages of insurance service purchase decision making, where one’s intellect and income determine the inclination towards insurance and where the price and quality of an insurance service determine its purchase decision. The research reveals a relatively equivalent impact of both consumers’ intellect and income on their inclination towards insurance in general; however, it strongly indicates the consumers’ strong focus on the price of the service as opposed to its quality when deciding to purchase an insurance service. The research also discloses the higher complexity of the decision making process when purchasing life insurance services as compared to non-life insurance services.Key words: insurance consumer behaviour rationale, insurance service purchase inclination and decision stages, intellect vs. income, price vs. quality, complicated vs. trivial process